Prophylactic approach against tuberculosis in HIV-Infected patients in the outpatient service of philanthropic hospital - Nogueira, Carolina T.; Abrantes, Julieta L.; Frauches, Diana O.; Borges, Luís Henrique B. (Brazilian Journal of Sexually Transmitted Diseases, 2009)
Introduction: tuberculosis is one of the main opportunistic diseases which affect HIV/aids patients. In order to reduce the risk of developing tuberculosis in these patients, the Brazilian Health Ministry recommends an annual tuberculin skin test, aimed at establishing oportune preventive therapy (PT). This approach can be considered a parameter of evaluation of the quality of a health service. Objective: analysing the prophylactic approach against tuberculosis in HIV-infected patients in an outpatient clinic of philanthropic hospital. Methods: retrospective study of HIV/aids patients’ medical records which were monitored in the Infectious and Parasitary Diseases Ambulatory of the Santa Casa da Misericórdia in the city of Vitoria, in December, 2007. Factors that could condition the solicitation of PPD were explored and descriptive analisys was made of the cases in which PT was done, and of tuberculosis cases as well. Results: within the study population of 361, those that had tuberculosis before or up until the first three months from the beginning of the monitoring were excluded and 334 patients were selected. The average monitoring time was 5.77 years and the average number of PPD per patient was 1.42, considering that 23.35% of the patients had no solicitation for PPD. Out of 178 results of the first PPD recorded, 22 were positive. PT was established in 37 cases and there was an occurrence of 15 cases of tuberculosis post-monitoring, corresponding to an incidence of 4.5%. Conclusion: failures in the preventive approach against tuberculosis were observed, as well as the precariousness of medical record keeping, affecting the quality of care directly. Improving the medical approach in reducing the risk of tuberculosis in HIV/aids patients is important.